Removal of Pseudomonas fluorescens biofilms from pilot-scale food processing equipment using ozone-assisted cleaning-in-place - Tirpanci Sivri, Goksel; Abdelhamid, Ahmed G.; Kasler, David R.; Yousef, Ahmed E. (Frontiers in Microbiology, 2023)
Biofilm formation in food processing environment and within equipment increases the risk of product spoilage and contamination with pathogens. Cleaning-in-place (CIP) operations are useful in removing soils and sanitizing processing equipment, including eliminating biofilms. However, CIP is a resource-intensive process, particularly in the usage of chemical detergents, heat, and sanitizers. The current study was initiated to investigate the feasibility of integrating ozone into CIP operations to facilitate the elimination of Pseudomonas biofilm, with the long-term goal of decreasing the dependance on conventional cleaning and sanitizing reagents. To investigate integrating ozone into CIP, a robust biofilm of Pseudomonas fluorescens was developed on a pilot-scale food processing equipment after two days of incubation in 10% skim milk (skim milk-water mixture, 1:9 v/v) under stagnant conditions, followed by additional five days of circulation while feeding 10% fresh skim milk. CIP was applied using water prerinse at 22-25°C, alkaline cleaning with 0.2% potassium hydroxide at 50°C, and a final water rinse. These CIP operations reduced planktonic cell populations below the detection method’s limit but did not fully remove P. fluorescens biofilm from either smooth or rough surfaces of the processing equipment. When the CIP process was followed by application of an aqueous ozone step (10 ppm for 10 min), the treatment reduced biofilm cell population, on smooth and rough surfaces, below the recovery method’s detection limit (0.9 and 1.4 log CFU/ 100 cm2, respectively). These findings demonstrate the utility of ozone-assisted CIP in eliminating microbial biofilms on processing equipment, but further research is needed to optimize the use of cleaning agents and the application of ozone.